2017
DOI: 10.4103/aam.aam_7_17
|View full text |Cite
|
Sign up to set email alerts
|

Emerging trends of nosocomial pneumonia in intensive care unit of a tertiary care public teaching hospital in Western India

Abstract: Background:Nosocomial pneumonia poses great challenge to an intensivist. Detailed information about hospital-acquired pneumonia (HAP) and ventilator-acquired pneumonia (VAP) is crucial for prevention and optimal management, thus improving quality Intensive Care Unit (ICU) care. Hence, we aimed to study the current trend of nosocomial pneumonia in ICU.Materials and Methods:It was a prospective observational cohort study, conducted in the ICU of a tertiary care teaching public hospital over a period of 18 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…HAP is a common hospital-acquired infection with a prolonged hospital length of stay and high patient mortality [1]. HAP is associated with a mortality rate ranging from 20% to 60%, especially in the ICU [79]. The attributable mortality is probably higher in some specific populations such as patients with chronic obstructive pulmonary disease (COPD) [10] and psychiatric diseases [11].…”
Section: Introductionmentioning
confidence: 99%
“…HAP is a common hospital-acquired infection with a prolonged hospital length of stay and high patient mortality [1]. HAP is associated with a mortality rate ranging from 20% to 60%, especially in the ICU [79]. The attributable mortality is probably higher in some specific populations such as patients with chronic obstructive pulmonary disease (COPD) [10] and psychiatric diseases [11].…”
Section: Introductionmentioning
confidence: 99%
“…Klebsiella and E. Coli are common nosocomial pathogens both worldwide and in India, and are often MDR. [ 9 10 ] Hospital-acquired Klebsiella can be harbored in the conjunctiva and sometimes cause serious ocular infection in patients during the hospital stay. [ 11 ] The Klebsiella and E. Coli isolate in this case was extended drug resistant and sensitive only to colistin.…”
Section: Discussionmentioning
confidence: 99%
“…These organisms are notorious for being multi-drug resistant (MDR). [ 9 10 ] Since the exudates are trapped in the potential space between the donor cornea and host Descemet membrane (DM), surgical management in the form of therapeutic penetrating keratoplasty (TPK) is often required. [ 5 ]…”
mentioning
confidence: 99%
“…[18] Studies from ICUs in Egypt and India found Klebsiella to be the most common organisms associated with ventilator-associated pneumonia (VAP). [19,20] The ICU where the present study was conducted does not formally adhere to any 'ventilator care bundle' , and VAP rates might have been underestimated. However, endotracheal-tube colonisation by Pseudomonas is a well-established phenomenon; a recent study investigating the microbiome of endotracheal tubes showed that the presence of Pseudomonas in the endotracheal tube showed a strong correlation with the poor prognosis of ICU patients.…”
Section: Discussionmentioning
confidence: 99%